Best practice for character education for millennial generation: The correlation between Pancasila values and Indonesian Muslim families - Riyanti, Rika; Haris, Didik M Nur; Nurmala, Nurmala (International research journal of management, IT and social sciences, 2022)
The discussion about best practices in shaping character for the millennial generation about Pancasila values and Muslim family education is an exciting topic to be discussed in various contexts and content. To discuss this issue, we have conducted a series of searches for supporting data and additional information electronically on literature sources in the form of field study findings that actively discuss best practices in shaping the character of the young Muslim generation concerning Pancasila education and the habits of Muslim families in Indonesia. We cannot use this data to answer questions with high times. After a summary of the data and an in-depth discussion of the relationship between the two variables, the researcher can finally conclude that there are some best practices in shaping the character of the millennial generation, in this case, looking for a correlation between Pancasila education and Indonesian family education to form a young age that follows the character Islamic nation and religion. Thus, it is hoped that these findings will add to the wealth of knowledge and perspectives of family religious education and are also in line with Pancasila education as Muslim Indonesian citizens.